Evaluation of vitamin B6 supplementation in Wilson’s disease patients treated with D-penicillamine - Olivier Guillaud; Alain Lachaux; Justin Mbala; Abdelouahed Belmalih; Eduardo Couchonnal Bedoya (BMJ Open Gastroenterology)
Introduction Wilson’s disease (WD) is a copper metabolism disorder characterised by a progressive accumulation of this metal mainly in the liver and the brain. Treatment is based on the removal of copper operated by the chelators, among which, D-penicillamine (DP) is prescribed as a first-line treatment in most situations. There is some evidence in linking the use of DP with a risk of vitamin B6; therefore, vitamin supplementation is sometimes recommended, although non-consensually. The objective of our study was to evaluate the level of vitamin B6 in WD patients treated with DP with and without associated supplementation.Methodology All WD patients followed at the National Reference Centre for WD in Lyon between January 2019 and December 2020 treated with DP for more than 1 year were included and separated in two groups according to vitamin B6 supplementation. The level of vitamin B6 was measured by the determination of pyridoxal phosphate (PLP).Results A total of 37 patients were included. Average age of 23.3±14.8 years, 15 patients with <18 years. Median duration of treatment was 51 (55.8) months. 15 patients were under vitamin B6 supplementation and 22 had interrupted it for more than 1 year. The median PLP level was significantly higher in the group with supplementation, 137.2 (86.7) nmol/L vs 64.9 (30.8) nmol/(p<0.01). No patient had a PLP level<35 nmol/L.Conclusion Long-term stable WD patients under DP treatment probably do not need vitamin B6 supplementation.